Food irradiation : a technique for preserving and improving the safety of food - World Health Organization (Geneva : WHO, 1988)
A factual, objective, and authoritative account of the role of food irradiation as a technique for improving food safety and reducing food losses. Written in non-technical language, the book attempts to give consumers, consumer protection groups, and government officials the facts they need to form an opinion about the acceptability of irradiated foods. To this end, chapters draw upon extensive scientific evidence, supported by practical experiences in more than 30 countries, to explain what the process is, how it works, and what it will and will not do. Throughout, information and explanations are guided by a genuine respect for the fears of consumers, particularly concerning questions of safety and quality. Prepared by a group of 10 international experts, checked for technical accuracy by several food safety institutions, and backed by the authority of FAO and WHO, the book should do much to promote public understanding as the only reliable path towards general acceptance and fuller use of food irradiation for the benefit of mankind.
Keywords: Food Irradiation; Food Preservation; Food Safety